Goodwin, Baumol & Lewis: How structural change can lead to inequality and stagnation - Codrina Rada; Ansel Schiavone; Rudiger von Arnim (The University of Utah, Department of Economics, 2021)
This paper presents a classical-Keynesian one sector model of labor-constrained growth that explains secular stagnation as the result of structural change. Structural change is defined as an exogenous increase in the employment share of stagnant activities, which exhibit no or low labor productivity growth. We discuss two models: (i) a classical distributive cycle in employment rate and labor share, and (ii) a Keynes-Kalecki distributive cycle that adds the incomecapital ratio as state variable. Both versions consider labor productivity growth as endogenous to the labor share, reminiscent of induced technical change. Further, growth rates of labor productivity and real wages are assumed to respond negatively to structural change as proxied by the employment share of stagnant activities. Drawing on seminal theories of structural change, we label the positive (negative) difference between these effects dominant Lewis (Baumol) dynamics. In steady state, and across all model variants, the adverse effect of structural change on labor productivity leads to stagnation. However, only the Keynes-Kalecki version with dominant Lewis dynamics and a weak profit squeeze also exhibits a falling labor share.
Keywords: E12; E25; E32; O41; 330; Goodwin cycle; stagnation; structural change; reserve army